An Update on Ocular Surface Epithelial Stem Cells: Cornea and Conjunctiva - Tiago Ramos; Deborah Scott; Sajjad Ahmad (Stem Cells International)
The human ocular surface (front surface of the eye) is formed by two different types of epithelia: the corneal epithelium centrally and the conjunctival epithelium that surrounds this. These two epithelia are maintained by different stem cell populations (limbal stem cells for the corneal epithelium and the conjunctival epithelial stem cells). In this review, we provide an update on our understanding of these epithelia and their stem cells systems, including embryology, new markers, and controversy around the location of these stem cells. We also provide an update on the translation of this understanding into clinical applications for the treatment of debilitating ocular surface diseases.